2022
DOI: 10.1039/d1fo02855c
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium and molybdenum co-induce pyroptosis and apoptosis via the PTEN/PI3K/AKT axis in the livers of Shaoxing ducks (Anas platyrhynchos)

Abstract: Cadmium (Cd) and excessive molybdenum (Mo) have adverse impacts on animals. However, the hepatotoxicity co-induced by Cd and Mo in ducks has not been fully elucidated. In order to explore...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 83 publications
2
14
0
Order By: Relevance
“…Then, we detected the related indices and found that Cd could dramatically up-regulate the expression of IL-18, IL-1β, NLRP3, ASC and caspase-1, and the fluorescence signal of the interaction between NLRP3 and ASC was clearly enhanced, which meant that Cd activated NLRP3 inflammasome. Based on the concentration of Cd in the environment, Cao et al fed ducks with a basal diet containing 4 mg/kg Cd for 16 weeks and the results suggested the expression of NLRP3, ASC, IL-18 and IL-1β was significantly increased, resulting in liver inflammation, which is consistent with our results [ 42 ]. In addition, the co-treatment of Se and Cd could greatly ameliorate the above changes and lower the expression level of NLRP3 inflammasome and other related inflammatory factors.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Then, we detected the related indices and found that Cd could dramatically up-regulate the expression of IL-18, IL-1β, NLRP3, ASC and caspase-1, and the fluorescence signal of the interaction between NLRP3 and ASC was clearly enhanced, which meant that Cd activated NLRP3 inflammasome. Based on the concentration of Cd in the environment, Cao et al fed ducks with a basal diet containing 4 mg/kg Cd for 16 weeks and the results suggested the expression of NLRP3, ASC, IL-18 and IL-1β was significantly increased, resulting in liver inflammation, which is consistent with our results [ 42 ]. In addition, the co-treatment of Se and Cd could greatly ameliorate the above changes and lower the expression level of NLRP3 inflammasome and other related inflammatory factors.…”
Section: Discussionsupporting
confidence: 90%
“…Studies have shown that Cd is hepatotoxic and can cause hepatocyte damage [ 35 , 42 ]. When hepatocytes are damaged, the permeability of the cell membrane increases and the release of LDH and transaminases (ALT and AST) rises, which is an essential indicator for evaluating liver damage [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…They can accumulate after entering the body, and affect the absorption of other trace elements, and finally destroy trace elements balance. Our previous researches confirmed Mo and Cd combined exposure resulted in the distinct increase of Mo and Cd concentrations and decrease the concentrations of Fe, Se, Cu and Zn in duck livers and kidneys 37,38 . In the present study, data verified that Mo or/and Cd obviously elevated their contents in lung, and decreased Cu, Fe, Se and Zn levels and the alteration were most notable in the co‐treated group, further confirming that excess Mo and Cd are cumulative poisons and can lead to the destruction of trace elements homeostasis.…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, Se might inhibit oxidative stress and recover autophagy flux, finally preventing the liver cell pyroptosis. In another study, Cao et al [ 99 ] reported that cadmium and molybdenum induced pyroptosis and apoptosis via PTEN/PI3K/AKT signaling in duck liver tissue; however, the relationship between apoptosis and pyroptosis was not reported, and how autophagy regulated pyroptosis and apoptosis was also not explained. That study suggested that the most important function of PTEN is to block the activation of the PI3K-AKT-m-TOR signaling pathway via its lipid phosphatase activity [ 99 ].…”
Section: The Toxicity Of Cadmium Toward the Kidney Liver Bone And Brainmentioning
confidence: 99%
“…In another study, Cao et al [ 99 ] reported that cadmium and molybdenum induced pyroptosis and apoptosis via PTEN/PI3K/AKT signaling in duck liver tissue; however, the relationship between apoptosis and pyroptosis was not reported, and how autophagy regulated pyroptosis and apoptosis was also not explained. That study suggested that the most important function of PTEN is to block the activation of the PI3K-AKT-m-TOR signaling pathway via its lipid phosphatase activity [ 99 ]. In that study, the results indicated that cadmium induced PTEN activation and inhibited PI3K/AKT signaling, allowing us to speculate that cadmium might promote autophagy development, but prevents autophagy degradation, causing pyroptosis and apoptosis.…”
Section: The Toxicity Of Cadmium Toward the Kidney Liver Bone And Brainmentioning
confidence: 99%